One-step synthesis of Zn4Sb3nanocrystals and Zn4Sb3-ZnSb composites - Sudarat Sitthichai (2018)
Zn 4 Sb 3 nanocrystals were synthesized by a 900 W microwave of 4.5:3 M ratio Zn:Sb with a total mass of 1 g for 5 min. Phase, internal texture, constituents, vibration mode and energy gap were detected using X-ray diffraction (XRD), scanning electron microscopy (SEM) equipped with energy dispersive X-ray (EDX) spectroscopy, transmission electron microscopy (TEM), Raman spectroscopy and UV-visible spectroscopy. In this research, Zn 4 Sb 3 nanocrystals with a prominent vibration mode at 144 cm -1 and 1.22 eV optical band gap were detected, including Zn 4 Sb 3 -ZnSb composites were also synthesized using microwave plasma for 10 min. © 2013 Elsevier Ltd. All rights reserved.